Geo-physical attributes of Shushunia’s aquifer, Chhatna block, Bankura district, West Bengal, India - Bhutia, Namgyal Tshewang; Sinha, Malavika (Acta Geographica Debrecina Landscape & Environment series, 2023)
Shushunia hill lies in a transitional zone of the South Singbhum Mobile Craton and northern Gondwana formation. The Shushunia hill appears like a porcupine peak and it has structural similarity to the Eastern Ghat. The Shushunia hill zone is an example of a contact spring. In the foothill zone, two perennial springs are observed. The study purely deals with its aquifer and water quality. Based on the present rock strata and the nature of the contact aquifer, its early condition has been assumed. The discharge of the confined aquifers occurs by leakage. The water temperature depicts the springs are not of geothermal origin. Shushunia’s aquifer is the shallow flow system water table and it is the subdued replica of surface topography. The comparatively high discharge rate during post-monsoon indicates the fractured conduit-water seepage towards the aquifer. Moreover, twin-contact aquifers do not yield water uniformly. The perennial aquifer may act as a municipal water supply source for drinking purposes in the future.